Sources in European Political History - Cook, Chris. author. aut Link
XII, 190 p.
Keywords: This new publication constitutes the second volume in the widely-acclaimed Sources in European Political History. This latest volume provides a wide-ranging guide to the surviving private papers of over one thousand statesman, politicians and diplomats who played a part in the shaping of modern Europe.